Presidentialism in times of pandemic: Ecuador - Torres Maldonado, Ángel Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The Latin American states, traditional heirs to the presidential system of government, with certain combinations of figures typical of parliamentary systems, incorporate normative statements of divisionof powers. The constitutional reforms of recent years strengthen the executive's capacities for action and decision-making as a measure to overcome the democratic crises and the instability of political regimes. TheEcuadorian constitutions of 1998 and 2008 incorporate a vast recognition of rights and their guarantees, in addition, they attribute broad competencies to the Executive Function, to the detriment of the LegislativeFunction. The subtle institutional design provided for in the Ecuadorian Constitution of 2008 is aimed at consolidating a hyperpresidential system that concentrates political power. This article aims to: (i) reflecton the presidential system of government in times of pandemic; (ii) show that the Ecuadorian Constitution of 2008 goes beyond the essential characteristics of the presidential system of government; and (iii) propose measures to prevent the worrying moral crisis that has arisen in times of pandemic.